Petrogenesis and Ni-Cu sulphide potential of mafic-ultramafic rocks in the Mesoproterozoic Fraser Zone within the Albany-Fraser Orogen, Western Australia - Maier, W.; Smithies, R.; Spaggiari, C.; Barnes, S.; Kirkland, Chris; Yang, S.; Lahaye, Y.; Kiddie, O.; MacRae, C. (Elsevier BV, 2016)
The Albany Fraser Orogen is located along the southern and southeastern margins of the Archean Yilgarn Craton. The orogen formed during reworking of the Yilgarn Craton, along with variable additions of juvenile mantle material, from at least 1810 Ma to 1140 Ma. The Fraser Zone is a 425 km long and 50 km wide geophysically distinct belt near the northwestern edge of the orogen, hosting abundant sills of predominantly metagabbroic non-cumulate rocks, but including larger cumulate bodies, all emplaced at c. 1300 Ma. The gabbroic rocks are interpreted to have crystallised from a basaltic magma that had ∼8.8% MgO, 185 ppm Ni, 51 ppm Cu, and extremely low contents of platinum-group elements (PGE, <1 ppb). Levels of high field-strength elements (HFSE) in the least enriched rocks indicate that the magma was derived from a mantle source more depleted than a MORB source. Isotope and trace element systematics suggest that the magma was contaminated (εNd 0 to −2 throughout, La/Nb around 3) with small (<10%) amounts of crust before and during ascent and emplacement. Larger bodies of cumulate rocks show evidence for additional contamination, at the emplacement level, with country-rock metasedimentary rocks or their anatectic melts. The area has been the focus of considerable exploration for Ni–Cu sulphides following the discovery of the Nova deposit in 2012 in an intrusion consisting of olivine gabbronoritic, noritic and peridotitic cumulates, interlayered with metasedimentary rocks belonging to the Snowys Dam Formation of the Arid Basin. Disseminated sulphides from a drillcore intersecting the structurally upper portion of the intrusion, above the main ore zone, have tenors of ∼3–6.3% Ni, 1.8–6% Cu and mostly <500 ppb PGE, suggesting derivation from magma with the same composition as the regional Fraser Zone metagabbroic sills, at R factors of ∼1500. However, the Nova rocks tend to have higher εSr (38–52) and more variable δ34S (−2 to +4) than the regional metagabbros (εSr 17–32, δ34S around 0), consistent with the geochemical evidence for enhanced crustal assimilation of the metasedimentary country-rock in a relatively large magma staging chamber from which pulses of sulphide bearing, crystal-charged magmas were emplaced at slightly different crustal levels. Preliminary investigations suggest that the critical factors determining whether or not Fraser Zone mafic magmas are mineralised probably relate to local geodynamic conditions that allow large magma chambers to endure long enough to sequester country-rock sulphur.